A Multi-Institution Collaboration to Define Core Content and Design Flexible Curricular Components for a Foundational Medical School Course: Implications for National Curriculum Reform. (June 2019) - Chen, Sharon F.; Deitz, Jennifer; Batten, Jason N.; DeCoste-Lopez, Jennifer; Adam, Maya; Alspaugh, J. Andrew; Amieva, Manuel R.; Becker, Pauline; Boslett, Bryn; Carline, Jan; Chin-Hong, Peter; Engle, Deborah L.; et al.
Abstract : Medical educators have not reached widespread agreement on core content for a U.S. medical school curriculum. As a first step toward addressing this, five U.S. medical schools formed the Robert Wood Johnson Foundation Reimagining Medical Education collaborative to define, create, implement, and freely share core content for a foundational medical school course on microbiology and immunology. This proof-of-concept project involved delivery of core content to preclinical medical students through online videos and class-time interactions between students and facilitators. A flexible, modular design allowed four of the medical schools to successfully implement the content modules in diverse curricular settings. Compared with the prior year, student satisfaction ratings after implementation were comparable or showed a statistically significant improvement. Students who took this course at a time point in their training similar to when the USMLE Step 1 reference group took Step 1 earned equivalent scores on National Board of Medical Examiners–Customized Assessment Services microbiology exam items. Exam scores for three schools ranged from 0.82 to 0.84, compared with 0.81 for the national reference group; exam scores were 0.70 at the fourth school, where students took the exam in their first quarter, two years earlier than the reference group. This project demonstrates that core content for a foundational medical school course can be defined, created, and used by multiple medical schools without compromising student satisfaction or knowledge. This project offers one approach to collaboratively defining core content and designing curricular resources for preclinical medical school education that can be shared. Abstract : Supplemental Digital Content is available in the text.